(3GdeMce hGdeMjW GdCYXes - (3Ydj Hf ESeGYjd, GdeYQha HGHf pSjnOg, CHh GdMSf , GdVQjQ GdCfOdSj,J (B458 (3g` s
(3ChdgG (B:s
(3GdKGA hGdQGA (B: (3Yjf KQI hKQGQI hKQKGQI ZRjQI , hcPdc GdSMGHI hYjf KQI cKjQI GdOehY , hde JSeY ajgG KQKGQI s
(3BNQgG (B:s
(3hMci KYdH CjVkG Cf HYVge jbhd ChjJg ceG Cf GdhGh cPdc ced GdSaQ GdKGef hGdYTQhf , hHceGdg Je cJGH GdeMce ai GddZI HMeO Gddg s
(3GdfSNI GdKGfjI YTQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B215 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs